Using an Intersectional Lens on Vulnerability and Resilience in Minority and/or Marginalized Groups During the COVID-19 Pandemic: A Narrative Review - Siller, Heidi; Aydin, Nilüfer (Frontiers in Psychology, 2022)
Throughout the pandemic media and scholars have widely discussed increasing social inequality and thereby publicly pointed to often hidden and neglected forms of inequality. However, the “newly” arisen awareness has not yet been put into action to reduce this inequality. Dealing with social inequality implies exploring and confronting social privileges, which are often seen as the other side of inequality. These social constructs – inequality and privilege – are often discussed in the light of vulnerability and resilience. This is particularly important in the context of the worldwide Covid-19 pandemic and the efforts to end the pandemic as both constructs are discussed regarding access to health care, access to vaccination, access to education and knowledge, misinformation, social resources, economic resources and so forth. Minority and/or marginalized groups may be particularly vulnerable to the impact of the Covid-19 pandemic. However, resilience factors in these groups may be neglected and under-reported. This narrative review aims at illustrating the specific and intertwined aspects of resilience and vulnerability in minority and/or marginalized groups during the Covid-19 pandemic. To achieve this, we use an intersectional lens based on the recommendations made by Moradi & Grzanka. 48 articles were included in the narrative review. Most of them were commentaries focusing on social inequality and vulnerability and/or resilience. Based on the dissection of articles on structural, systemic and individual levels, we propose three hypothesis on vulnerability and resilience in minority and marginalized individuals and groups: 1) Social inequality must be considered on a global level: Inequality on a global level translates to the vulnerability of an individual; 2) Vulnerability is historically situated: Vulnerability (experienced in the pandemic) is maintained and reinforced by history; 3) Strength through collective (historical) hardship: Vulnerability is not the opposite of resilience but may serve as resilience aspect. The conclusions drawn from this review show that we need to include diverse voices to advance concepts such as vulnerability and resilience in minority and marginalized groups. Additionally, these concepts are not necessarily in opposition to each other, but vulnerability should be understood as integral part of resilience.